Prediction of ice skating performance with off-ice testing in women's ice hockey players - Bracko, M. R; George, J. D. (The Journal of Strength and Conditioning Research, 2001)
Off-ice predictors of skating performance have not been investigated for women's hockey players. The purpose of this study was to identify the off-ice variables associated with high-performance skating acceleration, speed, agility, and on-ice anaerobic capacity and power in women's ice hockey players. Sixty-one women's ice hockey players between the ages of 8 and 16 years ( age = 12.18 ± 2.05 years, playing experience = 4.68 ± 2.69 years) participated in the study. Subjects were 1-4 months postseason. Some players were continuing to play once per week during the off-season. Skating tests (ST) included (a) 6.10-m acceleration, (b) 47.85-m speed, (c) agility cornering S turn, and (d) modified repeat skate test (MRS). Two trials of each ST were measured with a photoelectric timing system (except MRS, which was measured with 1 trial). The off-ice variables that were evaluated included age, years of playing experience, height, body mass, predicted fat percentage, sit-and-reach flexibility, vertical jump height, 40-yd dash time, and 1-minute timed sit-ups and push-ups. The results of this study show that 40-yd dash time is the strongest predictor of skating speed in women's hockey players ages 8-16 years old. From the regression procedure the best prediction equation was speed = 4.913 (0.0107 × kilograms) + (0.4356 × 40-yd dash time).